Alcohol Consumption Patterns in Alcohol Dependent Patients at Thai Army General (Phramongkutklao) Hospital - Daengthoen, Laddawan; Saengcharnchai, Pichai; Yingwiwattanapong, Jatsada; Perngparn, Usaneya (Journal of Health Science of Thailand, 2017)
The purpose of this study was to explore the pattern of alcohol consumption among alcoholdependent patients, including 124 participants admitted to the Thai Army General (Phramongkutklao) hospital for the treatment of alcohol withdrawal symptom from March to December, 2011. The participants were assessed using the 4th Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) to diagnose alcohol- dependence and the Alcohol Use Disorder Identification Test (AUDIT) to determine the level of alcohol addiction. Their alcohol-drinking behaviors were appraised by researcher’s questionnaire-surveying on theirs demographic and socioeconomic data, alcoholdrinking behavior and impacts of alcohol drinking. Results revealed that the average AUDIT score were 28. Most of them were male, average age was 46.3 years, 58.1 percent were married, 66.9 percent were graduated from secondary school, and 62.9 percent were army officers. The average age of firstly was 18.5 years, while the number of years on drinking was 27.4 years, and the median of the amount of liqueur they drank was 118.5 gm. per day. Regarding the type of alcohol, the most consumption was spirit, followed by many types at a time, for example, beer, spirit, and white spirit. They drank almost daily, especially on working days, before and after work. Their main reasons of drinking ranged from relaxation, fun, celebration, to health. Almost half of them did not realize or were not concerned about abstinence, although they had already known about its implications related to their health, work, finance and families. As for the alcohol dependence, letting the community take care of them after the treatment by public health professionals would be a more effective prevention against their relapses.